Imaging of nuclear Overhauser enhancement at 7 and 3 T. (24th May 2017) - Shen, Yuanyu; Xiao, Gang; Shen, Zhiwei; Zhang, Xiaolei; Tang, Xiangyong; Hu, Wei; Zhang, Zhiyan; Guan, Jitian; Wu, Renhua
Abstract : Nuclear Overhauser enhancement (NOE) is a type of magnetization transfer using cross‐relaxation. It originates from mobile macromolecules, which may have relevance to the evaluation of tumor features. We studied the value of NOE imaging at 7 and 3 T and suggest a utility for diagnosing human brain tumors. Two types of protein solution at different concentrations and pH values, and six normal Sprague Dawley (SD) rats, were used to detect NOE signal with a 7 T scanner. Then, six healthy volunteers and 11 patients with brain tumors (six gliomas and five meningiomas) were included at 3 T. Z ‐spectra were measured and NOE weighted (NOE*) images were acquired with a three‐offset measurement. Wide spectral separation was shown at both 7 T and 3 T delineating the NOE peak in the Z ‐spectrum. The concentration dependence and pH independence of NOE were confirmed in phantom experiments, and NOE values were greater in white matter than in gray matter in vivo . At 3 T, data indicated that NOE* maps were slightly hypointense in gliomas and were not obviously different from meningiomas. Thus, NOE imaging may help distinguish benign from malignant tumors, and as such may contribute to diagnosing brain tumors. Abstract : Our study investigated NOE signals in human brain tumors at 3 T. We found that, in tumor core, NOE signals were attenuated in glioma and not in meningioma. However, in MTRaysm images, we observed that the tumor cores were hyperintense in both glioma and meningioma. NOE imaging may help distinguish benign from malignant tumors, and as such may contribute to diagnosing brain tumors.